DIDACTIC POSSIBILITIES OF USING COMPLEX INTEGRATION IN FORMING METACOGNITIVE SKILLS - Nоsirova Rana Khamidovna (Journals Park Publishing, 2024)
The article presents issues of reforming the system of preschool education in our country, through the development and improvement of educational institutions, metacognitive methods in educational activities.
Keywords: preschool education system, institution, the younger generation, mental, metacognitive, intellectual, spiritual development, preparation for school, improvement.